Open Dating of Foods. - Labuza, Theodore P. (Publications in food science and nutrition., 2008)
Open dating plays a vital role in the distribution of the food products from the farm or place of manufacturing to the consumer's home. One principle is that the shelf life is a function of the distribution conditions and can be looked at as the percentage of consumers a manufacturer is willing to displease. Thus, one purpose of an open date is to give consumers enough time to purchase a food product and store it at home for a reasonable period of time before the product reaches the end of shelf-life in terms of some degree of quality change that is still acceptable. If products are not stored.